2016
DOI: 10.1002/minf.201600012
|View full text |Cite
|
Sign up to set email alerts
|

In silicoExploration of the Conformational Universe of GPCRs

Abstract: The structural plasticity of G protein coupled receptors (GPCRs) leads to a conformational universe going from inactive to active receptor states with several intermediate states. Many of them have not been captured yet and their role for GPCR activation is not well understood. The study of this conformational space and the transition dynamics between different receptor populations is a major challenge in molecular biophysics. The rational design of effector molecules that target such receptor populations allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Nowadays, virtual screening can be also used to search for ligands tailored for distinct conformational states of GPCRs [ 104 ]. In this context Tarcsay et al [ 105 ] suggested that MD simulation is able to capture protein conformations which are less biased toward the binding points of the chemotype that has been crystalized to obtain the X-ray structure.…”
Section: High-throughput Docking As a Methods Of Virtual Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, virtual screening can be also used to search for ligands tailored for distinct conformational states of GPCRs [ 104 ]. In this context Tarcsay et al [ 105 ] suggested that MD simulation is able to capture protein conformations which are less biased toward the binding points of the chemotype that has been crystalized to obtain the X-ray structure.…”
Section: High-throughput Docking As a Methods Of Virtual Screeningmentioning
confidence: 99%
“…Bhattacharya and Vaidehi [ 107 ] used coarse grain computational methods to understand the modulation of the potential energy landscape of the β 2 adrenergic receptor by two full agonists, two partial agonists, and an inverse agonist, starting from the receptor crystal structure in complex with an inverse agonist, carazolol. Virtual screening with a salbutamol-stabilized conformation exhibited enrichment of non-catechol agonists over a norepinephrine-stabilized conformation which was produced by a different activation pathway [ 104 ]. Gandhimathi and Sowdhamini performed virtual screening and docking studies with both active and inactive state models of serotonin 5-HT 2A receptor obtaining agonist-like and antagonist-like molecules [ 92 ].…”
Section: High-throughput Docking As a Methods Of Virtual Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…These rearrangements lead to global structural changes towards conformational populations of active receptor states (induced fit mechanism) [ 21 ]. Most likely, both mechanisms contribute to a different extent to receptor activation depending on the ligand and receptor type [ 14 , 22 ]. Finally, receptors in an active state have a higher propensity to interact with intracellular partners.…”
Section: Complementing Static Datamentioning
confidence: 99%
“…One of the major advances in structure solution is the ability to solve the structures of membrane-bound G-protein-coupled receptors. This has dramatically changed the way these targets can now be prosecuted 83 , 84 .…”
Section: Recent Advances In Computer-assisted Drug Designmentioning
confidence: 99%